2022
DOI: 10.1080/14756366.2022.2121392
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 nanotube immobilised 5-lipoxygenase-mediated screening and isolation of anti-inflammatory active compounds from the leaves of lonicera japonica thunb

Abstract: In this work, a highly effective separation approach mediated by 5-Lipoxygenase (5-LOX) was established for screening and isolation of anti-inflammatory ingredients from leaves of Lonicera japonica Thunb. (LLJT). Using 5-LOX immobilised on TiO 2 nanotubes as a microreactor, the targeted screening was exploited by combining with HPLC-MS system. Four compounds confirmed as luteolin, luteoside, lonicerin, and isochlorogenic acid C and a fraction (M1) were screened out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Activation of Th2 cells drives the inflammatory response and its downstream factors coordinate allergic inflammatory cascade, including IgE synthesis and eosinophil survival and maturation [ 24 ]. Previous studies demonstrated that lonicerin had anti-inflammatory effect in vivo and in vitro , and for example, it reduced the levels of pro-inflammatory markers in the rat with ulcerative colitis and mice with acute lung inflammation and injury [ 15 , 19 , 25 ]. Our results revealed that lonicerin inhibited Th2 activation, which was evidenced by the decreased OVA-specific IgE, thereby reducing the inflammatory phenotype, including decreased mucus distribution and inflammatory index, reduced cell count, and lower inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Th2 cells drives the inflammatory response and its downstream factors coordinate allergic inflammatory cascade, including IgE synthesis and eosinophil survival and maturation [ 24 ]. Previous studies demonstrated that lonicerin had anti-inflammatory effect in vivo and in vitro , and for example, it reduced the levels of pro-inflammatory markers in the rat with ulcerative colitis and mice with acute lung inflammation and injury [ 15 , 19 , 25 ]. Our results revealed that lonicerin inhibited Th2 activation, which was evidenced by the decreased OVA-specific IgE, thereby reducing the inflammatory phenotype, including decreased mucus distribution and inflammatory index, reduced cell count, and lower inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, various Chinese patent medicine injections including LJT and the extracts are widely utilized for treating respiration-related disorders, which have made favorable curative effect. Louicera japonica Thunb extract (LTE) is rich in various chemical components, mainly for organic acids, including, Lut, chlorogenic acid, isochlorogenic acid, caffeic acid and palmitic acid [ 12 ]. Among them, Lut is a typical kind of natural flavonoid compound and an effective active monomer with strong oxidative capacity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%